Application research of distribution network based on quantum secure communication and 5G hard-slicing private network - Zhongping WU; Lujie WANG; Jianuo XU; Yanbo WANG; Liwei ZHANG (Dianxin kexue, 2022)
With its significant advantages of ultra-low latency, ultra-high bandwidth, and ultra-large-scale connection, 5G technology effectively compensates for the shortcomings of traditional optical fiber communication in the distribution network field, and provides a new network communication method for power distribution applications.However, the information security issues brought by the applications of 5G technology have appeared gradually.Based on this, a distribution network application scheme based on quantum secure communication and 5G hard-slicing private network was proposed.An end-to-end 5G hard-slicing private network for distribution network services was customized, and ensuring data transmission security by quantum secure communication technology.And this scheme has been deployed and verified in the actual distribution service network scenario, and the results showed that the average delay of 5G hard-slicing private network was 16.89 ms, the download sending and receiving rates were 380 Mbit/s and 371 Mbit/s, respectively, the upload sending and receiving rates were 31.2 Mbit/s and 30 Mbit/s, which meets the communication requirements of distribution network applications.Based on quantum secure communication technology, the quantum bit error rate was 0.75%, and the transmitted data can be encrypted and decrypted smoothly, which verified the feasibility of quantum secure communication and 5G hard-slicing technology in the distribution network.